Low-intensity continuous ultrasound to inhibit cancer cell migration - González, Itziar; Luzuriaga, Jon; Valdivieso, Alba; Candil, Manuel; Frutos, Jesús; López, Jaime; Hernández, Luis; Rodríguez-Lorenzo, Luis; Yagüe, Virginia; Blanco, Jose Luis; Pinto, Alberto; Earl, Julie (Frontiers in Cell and Developmental Biology, 2023)
In recent years, it has been verified that collective cell migration is a fundamental step in tumor spreading and metastatic processes. In this paper, we demonstrate for the first time how low-intensity ultrasound produces long-term inhibition of collective migration of epithelial cancer cells in wound healing processes. In particular, we show how pancreatic tumor cells, PANC-1, grown as monolayers in vitro respond to these waves at frequencies close to 1 MHz and low intensities (<100 mW cm−2) for 48-72 hours of culture after ultrasound irradiation. This new strategy opens a new line of action to block the spread of malignant cells in cancer processes. Despite relevant spatial variations of the acoustic pressure amplitude induced in the assay, the cells behave as a whole, showing a collective dynamic response to acoustic performance, agreeing with the “cell jamming” effect defined before in the literature. Experiments carried out with samples without previous starving showed remarkable effects of the LICUs from the first hours of culture, more prominent than those with experiments with monolayers subjected to fasting prior to the experiments. This new strategy to control cell migration demonstrating the effectiveness of LICUS on not starved cells opens a new line of action in vivo to block the spread of malignant cells. This is a proof-of-concept study to demonstrate the physical effects of ultrasound stimulation on tumor cell migration. An in-depth biological study of the effects of ultrasounds and underlying biological mechanisms is on-going but out of the scope of this article.